Variables that influence crowdfunding success - Johansen, Candace Ann (Kansas State University, 2019)
Crowdfunding is a novice method for entrepreneurs that are looking for a way to get funding for their projects. It allows creators of projects to fund their efforts by accepting contributions from a large number of individuals over the Internet without the usual financial intermediaries. The purpose of this project was to examine crowdfunding sites and what influenced campaigns to succeed or fail for authors or creators presenting campaigns with certain criteria. This research aimed to understand if animals used in crowdfunding campaigns would influence perceptions of backers. A qualitative exploratory content analysis was used to examine 24 crowdfunding campaigns from three popular crowdfunding platforms. In addition to extrinsic motivators, such as rewards, findings also revealed that a campaign video, updates, a compelling project page and a timeline were essential to the success of a campaign. The research showed that backers of projects were more concerned with the legitimacy of a project than anything else. They needed to know that there were real people behind the project so they wouldn’t be scammed. The research also showed that, at this time, the use of animals in crowdfunding campaigns doesn’t seem to be widespread compared to the use of animals in traditional media.
Keywords: Fundraising; Crowdfunding; Theory of Communication; Incentive Theory of motivation